Linear convergence of the NQZ algorithm for finding the H-spectral radius of nonnegative tensors - Hongbin Lv; Meixiang Chen (PLoS ONE, 2026)
The R -linear convergence of the NQZ algorithm for computing the H -spectral radius of a class of weakly irreducible nonnegative tensors is established by utilizing the directed graphs of tensors. Meanwhile, an upper bound for the root convergence factor R is derived and a general condition ensuring the linear convergence of the NQZ algorithm is provided.